The relationship between capacity and utilization of nonpharmacologic therapies in the US Military Health System - Rendelle Bolton; Grant Ritter; Krista Highland; Mary Jo Larson (BMC, 2022)
Abstract Background Nonpharmacologic therapies (NPTs) are recommended as first-line treatments for pain, however the impact of expanding professional capacity to deliver these therapies on use has not been extensively studied. We sought to examine whether an effort by the US Military Health System (MHS) to improve access to NPTs by expanding professional capacity increased NPT utilization in a cohort at higher risk for pain - Army soldiers returning from deployment. Methods Our study involved secondary analysis of MHS workforce data derived from the Defense Medical Human Resources System Internet (DMHRSi), and healthcare utilization data obtained from two ambulatory record systems of the Military Health System (MHS) for a sample of 863,855 Army soldiers previously deployed to Iraq or Afghanistan over a 10-year period (2008-2017). We measured clinical provider capacity in three occupational groups responsible for pain management at 130 military treatment facilities (MTFs): physical therapy, chiropractic, and behavioral health, measured annually as full-time equivalence per 100,000 patients served at each MTF. Utilization in both direct and purchased care settings was measured as annual mean NPT users per 1000 sample members and mean encounters per NPT user. Generalized estimating equation models estimated the associations of facility-level occupational capacity measures and facility-level utilization NPT measures. Results In 2008, nearly all MTFs had some physical therapist and behavioral health provider capacity, but less than half had any chiropractor capacity. The largest increase in capacity from 2008 to 2017 was for chiropractors (89%) followed by behavioral health providers (77%) and physical therapists (37%). Models indicated that increased capacity of physical therapists and chiropractors were associated with significantly increased utilization of six out of seven NPTs. Acupuncture initiation was associated with capacity increases in each occupation. Increased professional capacity in MTFs was associated with limited but positive effects on NPT utilization in purchased care. Conclusions Increasing occupational capacity in three professions responsible for delivering NPTs at MTFs were associated with growing utilization of seven NPTs in this Army sample. Despite increasing capacity in MTFs, some positive associations between MTF capacity and purchased care utilization suggest an unmet need for NPTs. Future research should examine if these changes lead to greater receipt of guideline-concordant pain management.